2013
DOI: 10.5861/ijrsll.2013.561
|View full text |Cite
|
Sign up to set email alerts
|

Motivation and learner variables: Group differences in college foreign language learners' motivations

Abstract: In this study, the researchers surveyed 130 language learners enrolled in first-year foreign language classrooms in a public university in Utah, United States. This study intended to address the following research questions: (1) What motivational factors are found among learners enrolled in first-year foreign language courses at the university level in the United States?, (2) Do first-year language learners' motivations differ based on the following learner variables: (a) gender, (b) language being learned, (c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…With regard to gender differences in language learning motivation, this study found no significant difference between female and male students in their English learning motivation, which conformed to other findings in the literature showing no difference between motivation levels of males and females [23]. However, this finding contradicts with the results of other studies which reported higher levels of motivation for females than males for learning a second language [18,19].…”
Section: Discussionsupporting
confidence: 62%
See 4 more Smart Citations
“…With regard to gender differences in language learning motivation, this study found no significant difference between female and male students in their English learning motivation, which conformed to other findings in the literature showing no difference between motivation levels of males and females [23]. However, this finding contradicts with the results of other studies which reported higher levels of motivation for females than males for learning a second language [18,19].…”
Section: Discussionsupporting
confidence: 62%
“…These findings also supported the view in the literature. Similarly, Sung and Tsai [23] also found that learners' interest in culture, travel, people, and positive learning attitudes/experience are two important predictors of future foreign language learning. In the same line, Wen's [1] study also displayed the fact that positive learning attitudes/experience is a strong predictor of learners' desire to continue foreign language learning.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations